Pengaruh Pelatihan dan Motivasi Kerja Terhadap Kinerja Karyawan Pabrik Gula Pesantren Baru Kediri - Muhammad Yasin; Mahfudiyanto Mahfudiyanto (BIMA : Journal of Business and Innovation Management, 2018)
The purpose of this study is to determine the effect of Training and Work Motivation on Employee Performance at Pesanteren New Kediri Sugar Factory, either simultaneously or partially. The study population is 303 permanent employees. Technique Sample proportional random sampling, with respondents 75 people. The method of data analysis is descriptive analysis method of verivikatif and multiple linear regression. Based on the results of the research obtained multiple linear regression equation Y = 7,567 + 0.185 X1 + 0.447 X2. Using the SPSS 23 The results of the F test hypothesis show a F count of 27.610 ˃ Ftable (3.12) with a significance level of 0.000. Since the probability is significantly much smaller than 0.05 then Ho is rejected and Ha is accepted. This shows that simultaneously H3 which states that there is influence of training and work motivation together to the performance of employees received. Based on partial test results for training variables obtained Thitung = 2.462 ˃ Ttabel (1,666) significance of 0.016. <0.05 then Ho rejected and Ha accepted. This shows that partially H1 which states that there is influence of training on employee performance is accepted and work motivation variable is obtained Thitung = 5,545 ˃ Tabel (1,666) with significance value equal to 0.000. Since the probability is significantly much smaller than 0.05 then Ho is rejected and Ha is accepted. This shows that the partial H2 which states that there is influence of work motivation on employee performance is accepted. The coefficient of determination (Adjusted R2) is 0.418. It can be concluded that the contribution of training and work motivation to employee performance simultaneously is 41.8%. the performance of employees of Pesanteren New Kediri Sugar Factory is influenced by training and work motivation, while the rest is influenced by other variables that are outside the variables studied in this study.